A performance comparison of three micro-sized blade rotor designs for Malaysia wind speed condition - Rosmin, Norzanah (2015)
Vertical-Axis Wind Turbines (VAWTs) are known as the most suitable wind turbine for small-scale electrical generation. There are many types of VAWTs and each of it has different performances and efficiency. In this work, three types of VAWT systems (Savo-B2, Savo-B4 and Giro-B3) were designed, constructed and tested to investigate the amount of electrical power that could be generated under several constant wind speeds. The blade rotors were designed and built using 2 mm thickness of aluminum plate. The tip speed ratios, power coefficients, blade rotations for each blade rotor and the simplicity of the proposed designs were studied via an experimental setup. The experimental work demonstrates that Savo-B2 provides the highest power coefficient which is up to 0.32. Meanwhile, Giro-B3 offers the fastest rotational blade speed, up to 20.53 rad/s, among the three designs.